Fadia Faqir’s My Name is Salma: Witness to Patriarchy Persecution - Intisar Rashid Khaleel (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
My Name is Salma (2007) is a feminist trauma narrative that emphasizes Fadia Faqir’s desire to represent the experiences of voiceless women. Faqir’s writings mostly address the voices of those who have lost a loved one, usually describing and inscribing their words against a background of shock and forgetfulness. My Name is Salma, focuses on modern challenges, particularly those arising from the fallout of colonialism, postcolonialism, and fundamentalism. She may be the most qualified to articulate the components of voices, spaces, and traces. The focus on the voices of traumatized women may retrace the steps that those who have experienced loss have made in their quest for liberty, truth, and self-identification. For the voiceless Arab women, Faqir converts their silences into written testimonies highlighted in the neatly partitioned realm (Jordan, in particular). The lack of a unified sense of self represents fragmentation in this context